Impact of dry deposition flux and dust intrusion phenomena on elemental concentrations of air particulate matter - Dawood, Abdallah M. A.; Akortia, Eric; Alsufyani, Sultan J.; Gbeddy, Gustav (Frontiers in Environmental Science, 2023)
Depositions of trace elements of air particulates in the atmosphere have gained much attention in recent times due to their environmental, climatic and health impacts. In the current study, trace elements of size-segregated rural and urban particulate matter (〖PM〗_2.5 and 〖PM〗_(2.5-10)) were characterized using particle-induced X-ray emission method. Effects of dry deposition flux and Saharan dust intrusion on the elemental concentrations were determined. The mean elemental concentration in the rural fine PM ranged between 0.0002 ± 0.0002 µg m-3 (for Se) and 0.6658 ± 0.5816 µg m-3 (for S) whereas in the urban fine PM the concentration ranged between 0.0007 ± 0.0008 µg m-3 (for As) and 0.5869 ± 0.3429 µg m-3 (for Ca). In the coarse PM fraction, concentration ranged between 0.0001 ± 0.0001 µg m-3 (for Se) and 0.5886 ± 0.5343 µg m-3 (for Ca) at the rural site; and between 0.0002 ± 0.0002 µg m-3 (for Se) and 1.9201 ± 1.911 µg m-3 (for Ca) at the urban site. Mainly crustal elements (Al, Ca, Fe) and ‘pollution’ source element (S) recorded high and significant dry deposition fluxes across the two sites in both PM modes. Deposition flux was relatively higher in the coarse than in the fine PM mode. The average dry deposition flux estimated for fine and coarse PM at the rural and urban sites were 33.68 ± 57.19 µg m-2 day-1 and 47.71 ± 92.19 µg m-2 day-1; 36.66 ± 61.95 µg m-2 day-1 and 107.02 ± 237.71 µg m-2 day-1, respectively. Mainly crustal (Al, Ca, Fe) and ‘pollution’ (S) element recorded high and significant dry deposition fluxes across the two sites and in the two PM modes. Dust intruding the study area from the Sahara was analyzed using the NMMB/BSC dust model. The model result indicated that, the highest daily surface dust concentration was observed in the central and south-west of Turkey which corresponded with the peak period of Saharan dust transport to the Eastern Mediterranean in the month of March.